Hormonal and inflammatory modulatory effects of hesperidin in hyperthyroidism-modeled rats - Ashry, Mahmoud; Askar, Hussam; Obiedallah, Manar M.; Elankily, Ahmed Hussuin; Galal El-Sahra, Doaa; Zayed, Gamal; Mustafa, Mohamed A.; El-Shamy, Sawsan Abd El-Maksoud; Negm, Somaia A.; El-Beltagy, Marwa A.; Abdel-Wahhab, Khaled G.; Ene, Antoaneta (Frontiers in Immunology, 2023)
The goal of the current study was to determine whether hesperidin's ability to regulate immunological, inflammatory, and/or antioxidant regulatory systems can effectively prevent induced hyperthyroidism in female albino rats. To create four groups of ten adult female Wistar rats (weighing between 140 and 160 g apiece), the following criteria were used: Healthy mice were used as the control group in experiments 1 and 2. Healthy animals received intraperitoneal injections of hesperidin (50 mg/kg/day) for a period of six weeks. Hyperthyroidism-modeling animals were given no treatment. The findings showed that hesperidin significantly reduced the hyperthyroidism deteriorations, as evidenced by a large decline in serum T4, FT4, T3, and FT3 levels and a minor increase in TSH levels. Since hesperidin effectively decreased the level of TNF-, IL1-, IL4-, IL-6, and IL-10 and increased CD4+ level, this may be mediated by immunological, inflammatory, apoptotic, and/or antioxidant modulatory potentials. Additionally, there was a noticeable improvement in the oxidative status; the levels of SOD, GPx, CAT, and GSH were dramatically enhanced, and the levels of blood MDA and NO were decreased. Additionally, hesperidin demonstrated nephro-hepatoprotective and antiatherogenic potential by markedly lowering blood ALAT, ASAT, urea, creatinine, cholesterol, and triglyceride values to levels that were comparable to those of the healthy group. These findings were supported by histological and immunohistochemical data that showed a notable decrease in the expression of the calcitonin antibody. In conclusion, hesperidin has anti-hyperthyroidism, effectiveness; immune, inflammatory, apoptotic, and/or antioxidant regulatory processes may be how this effectiveness is mediated.